2020
DOI: 10.2169/internalmedicine.5074-20
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Glial Fibrillary Acidic Protein Astrocytopathy Presenting with Slowly Progressive Myelitis and Longitudinally Extensive Spinal Cord Lesions

Abstract: We report a 65-year-old man with autoimmune glial fibrillary acidic protein astrocytopathy (GFAP-A) who presented with gait disturbance that he had experienced for approximately half a year. On neurological examination, he displayed spastic paraplegia and autonomic dysfunctions including dysuria and constipation. Spinal cord magnetic resonance imaging showed longitudinally extensive spinal cord lesions (LESCLs) extending from the cervical to the thoracic cords. The patient was negative for anti-myelin oligoden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The reason for this is also uncertain. Myelitis in pediatric patients is relative rare compared adult patients [ 10 , 14 , 24 27 ]. In our case, the two patients with myelitis showed longitudinally extensive myelitic abnormalities, and a slight enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this is also uncertain. Myelitis in pediatric patients is relative rare compared adult patients [ 10 , 14 , 24 27 ]. In our case, the two patients with myelitis showed longitudinally extensive myelitic abnormalities, and a slight enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…Like the previous studies, most patients have an acute or subacute onset. Clinical manifestations were encephalitis and meningoencephalitis, including fever ( 45.4%), headaches (27.3%), dizziness (18.2%), drowsiness (18.2%), and mental disorders (18.2%) [3,9,10,13,14,15,16,17] . In our case, all of the patients who suffered from myelitis were showed longitudinally extensive transverse myelitis, like the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…The lesions were predominantly located centrally within the cord, affecting the grey matter, and characterized as hazy, subtle, or diffuse on T2weighted imaging [1,2,7,26,27]. Notably, three case reports described the lesions as bilateral longitudinal with an eccentric location [28][29][30].…”
Section: Spinal Cord Mri Findingsmentioning
confidence: 99%
“…Whereas some authors reported normal findings [25], even in areas with pathology on MRI [39,40], others reported increased or decreased uptake in different regions [27]. A few studies reported high intramedullary metabolism associated with extensive myelitis [29,37,41].…”
Section: Advanced and Nuclear Neuroimaging Findingsmentioning
confidence: 99%